(untitled) (Indian Journal of Animal Production and Management, 2013)
An investigation was undertaken to study the parturition behaviour of Swamp buffaloes of Assam. Data were collected from 30 animals of first to fifth lactation. Reduced interest in feed and water, restlessness, occasional raising of tail and abdominal straining were the most prominent signs observed during the first stage of parturition. During second stage of parturition animals showed restlessness and severe abdominal straining and they frequently lie down and got up. Majority of the animals (93.33%) delivered their foetus in standing position or on the way of attempting to stand. The pluriparous cows nursed their calves immediately after delivary. The average time recorded for the first, second, and third stages of parturition were 131.67±22.93, 30.93±3.60 and 248.33±22.28 minutes respectively. Total time required for the whole parturition process was 411.00±28.91 minutes. There was no significant effect of parity of animals as well as sex of the calves on various stages of parturition.